PREVENTION BEHAVIOR ABOUT COVID-19 RELATED TO THE ANXIETY LEVEL OF COMMERCIAL FLIGHT CABIN CREW IN INDONESIA - Aena Mardiah; Artha Budi Susila Duarsa; Dasti Anditiarina; Ayu Anulus (Universitas Airlangga, 2025)
Introduction: As of March 2020, Indonesia’s COVID-19 case fatality rate was 8.9%. Cabin crew are directly exposed to the consequences of the pandemic during flights. In addition, widespread flight cancellations have been associated with increased anxiety among employees. Aims: This study aimed to analyze the relationship between COVID-19 knowledge, attitudes, preventive behaviors, and anxiety among cabin crew in Indonesia. Methods: This cross-sectional study was conducted at the Aviation Health Center in Indonesia. A total of 314 cabin crew participated in the study and were recruited using consecutive sampling. Data on knowledge, attitudes, preventive behaviors, and anxiety were collected using online questionnaires. Bivariate and multivariate analyses were performed using Chi-square and logistic regression. Results: The majority of participants were female (79.6%) and aged 17-25 years (38.2%). In the multivariate analysis, poor preventive behavior remained a significant predictor of anxiety (aOR=2.63; 95% CI=1.14-6.02; p=0.023). Participants with negative attitudes had 1.55 times higher odds of experiencing anxiety compared to those with positive attitudes (aOR=1.55; 95% CI=1.10-2.17; p=0.010). Conclusion: Improving COVID-19–related attitudes and preventive behaviors among cabin crew may help reduce anxiety levels during flights.